Kajian karakteristik Mofometri dan Morfologi Daerah Aliran Sungai Antokan untuk Mengetahui Perkiraan Besarnya Limpasan Permukaan - Tuti Rezky (JURNAL BUANA, 2022)
Management watershed needs to be done unitedly by coordinating, consultation and communication between the parties, and therefore data and information on das' characteristics are indispensable to the management of the das. Particularly the characteristics of morphology and morometry are directly related to the response of rainwater that will become a surface stream. The purpose of research is (I) to examine the characteristics of morometeri das; (ii) assessed the characteristics of morphology das (iii) examined river basins' surface runoff. The study is a quantitative description that utilizes secondary data asa primary source of data and USES the cook's method in determining surface levels by scoring on 4 (the four physical parameters of slope slope, infiltration, land cover, and surface loading. According to research, the smaller classified river basins has a smooth stream of 1.28 km/km clarity, a marble (slope) das antokan is dominated by flat and gentle marbles, an estimated surface of das antokan that a value c or a coefficient value of 0.58 where 58% of the rainwater that falls into the area of antokan will become a surface stream, From this value you can conclude that the flow of the surface or the coefficient of the flow of the surface of the antokan river river could be marked high, the discharge of the top basin of the antokan river by 2, 5, and 10 years worth 503.4 m3/ second, 629.2 m3/ second, and 651.9 m3/ second. The calculation may be stated that ata 2-year anniversary of the duration of the rain (time of concentration) of 6.9 hours with a gradual humidity of 6.4 mm/ 2 millimeters of rain, the maximum discharge obtained on anthocyanin basin was 503.4 m3/ second.